Slovak Republic : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2007)
This Selected Issues paper on the Slovak Republic reviews efficiency and reform of the health sector. The immediate challenge for the health care system in the Slovak Republic is to improve health sector outcomes while containing public health spending. The Slovak health care system is decentralized, and the central government has limited control over decisions by insurance companies and health care institutions. The government has introduced limits on administrative costs of insurance companies and submitted proposals to regulate their profits with the aim of diverting resources to health care providers.